Foreign Portfolio Investment Control Using Macroeconomic and Institutional Policies: Evidence from Indonesia and Thailand - Zainuri, Zainuri (Universitas Dian Nuswantoro Semarang, 2021)
This study analyzed the influence of macroeconomic and institutional variables on foreign portfolio investment inflows in two ASEAN countries, Namely Indonesia and Thailand, in 2005 – 2019. The analytical tools used in this research are Panel Vector Error Correction Model (PVECM) and Panel Ordinary Least Square (POLS). The estimation results show that the macroeconomic variables that are proxied using inflation and openness economy and institutional variables that are proxied using the variable level of corruption and quality of regulation have a significant effect. In the long term, the inflation rate, the openness economy, and the quality of regulation variables significantly affect foreign portfolio investment. Meanwhile, in a short time, only the inflation rate variable and the openness ratio have a significant effect on foreign portfolio investment. The two analytical tools used found that macroeconomic and institutional variables consistently affect foreign portfolio investment.Keywords: Foreign portfolio investment, Inflation, Openness Economy ratio, CorruptionRegulation, PVECM, POLS